Clinical characterization of chronic chagasic cardiomyopathy in dogs - Pascon, João Paulo da E. [UNESP]; Pereira Neto, Gláucia B. [UNESP]; Sousa, Marlos G.; Paulino Júnior, Daniel [UNESP]; Camacho, Aparecido Antonio [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2010)
No continente Americano, aproximadamente 15 milhões de pessoas são afetadas pela doença de Chagas, ocasionando importantes danos econômicos e sociais. O cão é considerado excelente modelo experimental para o estudo dessa enfermidade; assim sendo, foram caracterizadas, neste ensaio, as anormalidades cardiovasculares de 13 cães experimentalmente infectados com a cepa Colombiana do Trypanosoma cruzi, em fase crônica (1997-2004). Ao eletrocardiograma, a arritmia sinusal respiratória foi o ritmo predominante durante todo período experimental (49,55-67%), com baixas prevalências de bloqueio de ramo direito (0-13%) e de bloqueio atrioventricular de primeiro grau (0-14%). A EcoDopplercardiografia espectral revelou inversão das ondas E e A mitral (0.71±0.17), confirmando a disfunção diastólica presente em todos os cães avaliados. O aumento da atividade enzimática sérica foi detectado, indicando agressão miocárdica pela infecção. Seis cães morreram durante o período experimental. Desta forma, a caracterização clínica dos cães experimentalmente infectados trouxe informações importantes, possibilitando reconhecer o comportamento clínico dessa importante infecção, na espécie canina.

On the American continent, almost 15 million people are affected by Chagas disease, resulting in important economic and social damages. Dogs are considered to be an excellent experimental model to study Chagas' disease; as a result, in this research, the characterization of cardiovascular abnormalities was performed in dogs experimentally infected with Trypanosoma cruzi (the Colombian strain) that were at chronic stage. Thirteen adult female dogs were evaluated by electrocardiographic, echocardiographic, hematological and biochemical analyses in the chronic phase. For the electrocardiographic studies, respiratory sinus arrhythmia was the predominant rhythm during the entire research period (49.55% to 67%), with a low prevalence of right bundle branch block (0-13%) and first-degree atrioventricular block (0-14%). The spectral Doppler echocardio-graphy showed E and A mitral wave reversal (0.71±0.17), confirming the diastolic dysfunction present in all dogs. An increase in the enzymes activities was detected in the serum analysis, indicating myocardial injury by the infection. Six dogs died during the follow-up. In this way, the clinical characterization of experimentally infected dogs, as described here, increases the knowledge and allows for recognition of the behavioural modifications present in Chagas' disease in affected dogs.
Keywords: Animal; Chagas disease; cardiomyopathy; Animal; Doença de Chagas; cardiomiopatia